Intensive cyclic chemotherapy and transplantation of autologous peripheral blood progenitor cells (PBPC) or whole blood in high-risk breast cancer — follow up at 10 years - Cinek, P.; Filip, S.; Vaňásek, J.; Měřička, P.; Bláha, M.; Zouhar, M. (Experimental Oncology, 2007)
Aim: The main aim of our paper is to contribute to objectification of currently widely discussed results of overall survival (OS), disease free survival (DFS) and time from relapse to tumor progression (TTP) in women with breast cancer. Methods: Forty consecutive patients fulfilling the eligibility criteria were admitted to the study. Fifty-six women were included in the control group. All patients received 6 cycles of adjuvant intensive cyclic combined chemotherapy with epirubicin 150 mg/m2 and cyclophosphamide 1250 mg/m2 (EC) applied each 14 days. To overcome haematological toxicity transplantations of autologous peripheral blood progenitor cells (PBPCs) or whole blood enriched of PBPC were used. Results: We found statistically significant difference in OS regardless of the stage of the disease to the benefit of women treated by intensive cyclic EC chemotherapy when compared with the control group. In evaluation of DFS no statistically significant difference was found in survival between the control group and the group with all stages of the disease. TTP in women without relation to the stage was statistically significantly longer than in the control group. Conclusion: In our study intensive cyclic EC chemotherapy did not show better curative effect when compared with conventional dosage chemotherapy. Цель:объективизация широко обсуждаемых результатов по общей выживаемости (OВ), периода ремиссии (ПР) и продолжительности периода от рецидива к опухолевой прогрессии (ПРОП) у больных раком молочной железы. Методы: обследовано 40 больных, отвечающих установленным критериям отбора, и 56 здоровых женщин, составивших контрольную группу. У всех больных проведено 6 циклов адъювантной интенсивной циклической комбинированной химиотерапии (эпирубицин — 150 мг/м2 и циклофосфамид — 1250 мг/м2 (ЭЦ)), проводимой каждые 14 дней. Для преодоления гематологической токсичности применяли трансплантацию клеток-предшественников периферической крови (КППК) или цельной крови, обогащенной КППК. Результаты: выявлены статистически значимые различия в ОВ, не зависящие от стадии заболевания, у пациенток, получавших интенсивную циклическую химиотерапию ЭЦ, по сравнению с контрольной группой. При оценке ПР не выявлено статистически значимых различий выживаемости между контрольной группой и больными во всех стадиях заболевания. ПРОП у пациенток независимо от стадии заболевания статистически значимо выше, чем таковой контрольной группы. Выводы: по результатам исследования, интенсивная циклическая химиотерапия ЭЦ не имеет лечебных преимуществ по сравнению со стандартной дозовой химиотерапией.